2001
DOI: 10.1097/00007890-200104150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Successful Preemptive Cidofovir Treatment for CMV Antigenemia After Dose-Reduced Conditioning and Allogeneic Blood Stem Cell Transplantation

Abstract: Our data suggest the feasibility of CDV administration in patients after allogeneic transplantation. In the recommended dose, it might be used successfully for low-risk patients, e.g., after DRC or organ transplantation, in an outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Two were nonresponders; one died from CMV pneumonia, and one developed CMV pneumonia that eventually responded to foscarnet. The less favorable outcome in the last two reports is in concordance with recent prospective results described by Platzbecker et al (75). In that study, only one of seven SCT recipients showed a transient clearance of pp65 Ag after treatment with CDV at 5 mg/kg/week for 2 weeks and thereafter every 2 weeks.…”
Section: CDVsupporting
confidence: 89%
See 1 more Smart Citation
“…Two were nonresponders; one died from CMV pneumonia, and one developed CMV pneumonia that eventually responded to foscarnet. The less favorable outcome in the last two reports is in concordance with recent prospective results described by Platzbecker et al (75). In that study, only one of seven SCT recipients showed a transient clearance of pp65 Ag after treatment with CDV at 5 mg/kg/week for 2 weeks and thereafter every 2 weeks.…”
Section: CDVsupporting
confidence: 89%
“…In that study, only one of seven SCT recipients showed a transient clearance of pp65 Ag after treatment with CDV at 5 mg/kg/week for 2 weeks and thereafter every 2 weeks. In contrast, those authors (75) showed that preemptive treatment with CDV was very successful in 10 SCT recipients treated with a nonmyeloablative conditioning regimen. Toxicity was moderate and consisted of reversible renal impairment (n ϭ 4), proteinuria (n ϭ 1), and nausea or vomiting (n ϭ 3).…”
Section: CDVmentioning
confidence: 92%
“…150,151 Cidofovir (generally used as a second-line anti-CMV agent) can be associated with substantial nephrotoxicity. 152,153 Acyclovir and valacyclovir have an excellent safety profile but are only weakly active against CMV.…”
Section: 133mentioning
confidence: 99%
“…In clinical trials cidofovir has proven efficacious not only against CMV retinitis but also against other manifestations of CMV disease, e.g., intravenously against asymptomatic CMV infection in HIV-infected patients (121,165). Cidofovir can be recommended as a preemptive treatment for CMV disease (i.e., treatment initiated if CMV antigen or DNA is detected in the blood) after allogeneic blood stem cell transplantation (163). In the study reported by Platzbecker et al (163), 9 (90%) of 10 patients showed a response to cidofovir treatment, with 7 of the 9 experiencing a complete clearance of the virus (pp65 negative, PCR negative); treatment-related toxicity was moderate, with 4 patients developing reversible renal impairment.…”
Section: Clinical Usefulness Cidofovirmentioning
confidence: 99%